A method for preparing a neodymium iron boron magnet
By adding metal carbides to the NdFeB magnet and forming a double-layer diffusion layer, combined with specific annealing treatment, the abnormal growth of Nd2Fe14B main phase grains caused by slow motion of the grain boundary diffusion source is solved, and the NdFeB magnet is significantly improved coercive force and magnetic properties.
Patent Information
- Application Number
- CN202411557491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
During the preparation of neodymium iron boron magnets, the slow motion of the grain boundary diffusion source causes abnormal growth of Nd2Fe14B main phase grains, reducing the coercive force of the magnet.
By adding metal carbides to NdFeB magnetic powder and forming a double diffusion layer during sintering, including a copper diffusion layer and a copper alloy diffusion layer, combined with a specific annealing treatment, a core-shell structure is formed to increase the thickness of the grain boundary layer and The diffusion efficiency of rare earth elements prevents abnormal growth of Nd2Fe14B main phase grains.
It significantly improves the coercive force and other magnetic properties of the neodymium iron boron magnet, enhances the grain spacing, avoids grain agglomeration, and improves the residual magnetic and magnetic energy accumulation of the magnet.
Smart Images

Figure CN119049872B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnet preparation, and in particular to a method for preparing a neodymium iron boron magnet. Background Art
[0002] NdFeB magnets are also called NdFeB rare earth permanent magnet materials. The magnet materials are obtained by sintering, bonding and hot pressing / hot deformation. NdFeB magnets have high coercivity and high magnetic energy level, so they can be widely used in wind power generation, electronic components, aerospace and new energy vehicles. NdFeB magnets are mainly composed of Nd2Fe 14 The main phase of NdFeB is composed of B-phase grains, Nd-rich phase and boron-rich phase. The Nd2Fe 14 B main phase grains, the neodymium-rich phase is distributed between the main phase grains, forming magnetic exchange coupling isolation, preventing the formation of reverse magnetization domain cores, and thus increasing the coercive force, so it is important to improve the Nd2Fe 14 The performance coercivity of the B main phase grains is mainly to improve the continuous and uniform distribution of the grains, perfectly space the grains, and reduce the exchange coupling between the grains.
[0003] In the prior art, before preparing NdFeB magnets, the surface of NdFeB powder is mainly modified by chemical methods, so that the surface morphology of the magnetic powder is changed, thereby reducing the corrosion and oxidation caused by the increased chemical activity of NdFeB powder under the influence of rare earth elements. For example, in the patent document with publication number CN117831926A, KH550 is used to modify the surface of NdFeB magnetic powder, which is beneficial to the adhesion of magnetic powder and resin, so that the magnet has good anti-oxidation effect. However, in the journal "Mining" 2022 NO.2, 83-87, Xiong Jun's research pointed out that when the amount of modifier added is 2%, the surface of NdFeB magnetic powder will show "disorderly distribution and obvious agglomeration phenomenon". In the subsequent sintering process, the silane coupling agent will accelerate hydrolysis under high temperature and high pressure to produce unnecessary impurities, introduce non-magnetic substances, and have a greater adverse effect on the improvement of the coercive force of the magnet.
[0004] Therefore, the grain boundary diffusion technology was developed on this basis. Initially, the fluidity of the grain boundary phase was increased to allow the neodymium phase to wrap around Nd2Fe 14 The B main phase grains achieve a significant jump in coercivity, and then add low melting point alloys for diffusion, thereby increasing the number of grain boundary phases to improve coercivity. Most of the latest research is to plate a layer of rare earth element Dy on the surface of NdFeB magnets by magnetron sputtering and then perform heat treatment to form (Nd, Dy)2Fe at the grain boundaries. 14B shell, improves the utilization rate of rare earth elements, for example, in the patent document with publication number CN117012537A, rare earth elements and metal elements are compounded to form a diffusion layer, and then powdered and applied to the surface of the NdFeB magnet for two-stage high-temperature treatment, forming a heavy rare earth-coated core-shell structure at the grain boundary of the NdFeB main phase, which improves the room temperature magnetic properties of the magnet. However, during the sintering process, the rare earth elements diffuse slowly in the neodymium phase. Under long-term heating treatment, Nd2Fe 14 The B main phase grains grow abnormally, and the grain structure is destroyed, resulting in loss of magnetism and decrease in coercive force. Summary of the invention
[0005] In order to solve the problem that the grain boundary diffusion source moves slowly during the grain boundary diffusion process, resulting in Nd2Fe 14 The B main phase grains grow abnormally, thereby reducing the coercive force of the NdFeB magnet. The present invention provides a method for preparing a NdFeB magnet, which specifically comprises the following steps:
[0006] S1. Smelting the alloy raw materials into alloy flakes, crushing them by hydrogen to obtain NdFeB magnetic powder, and mixing the NdFeB magnetic powder with metal carbides, wherein the addition ratio of the metal carbides is 1-3% of the weight of the NdFeB magnetic powder;
[0007] S2, the mixed magnetic powder is pressed to form a green embryo, and the green embryo is heat-treated to obtain a sintered NdFeB permanent magnet;
[0008] S3, performing double-layer evaporation plating, magnetron sputtering plating or multi-arc ion plating on the sintered NdFeB permanent magnet to form a double-layer diffusion layer, and performing heat treatment again, wherein the double-layer diffusion layer is a copper diffusion layer and a copper alloy diffusion layer;
[0009] S4. Perform the first annealing on the NdFeB permanent magnet covered with the double diffusion layer, the annealing temperature is 675-845°C, and the time is 2-3h; then perform the second annealing at a temperature of 400-500°C and keep the temperature for 4-5h to obtain the NdFeB magnet.
[0010] The present invention adds a specific amount of metal carbide to the components of NdFeB, and performs grain boundary diffusion on the basis of the rough blank obtained by preliminary firing to improve the performance of the NdFeB magnet. A precipitation coating treatment is performed on the surface of the rough blank to form a specific metal diffusion layer. During the heat treatment process, the copper in the diffusion layer diffuses first and forms a special low melting point phase with the metal carbide added previously for diffusion. Cu can fully wet Nd2Fe 14 The grain boundaries of the B main phase grains, which in turn helps the diffusion of the outer alloy elements in the double diffusion layer, fully diffuses in a short time, increases the thickness of the grain boundary layer, and eliminates the Nd2Fe 14 The abnormal growth of the B main phase grain unit cell increases the coercive force of the NdFeB magnet.
[0011] In addition to accelerating the diffusion of alloy elements by cooperating with the metal carbide and the double diffusion layer, the present invention can also dissolve and segregate the carbon element in the metal carbide through two annealing treatments at specific temperatures, so that the carbon atoms are stably dissolved in the grain boundary phase at high temperature. During the cooling process, the carbon atoms are segregated from the grain boundary phase to the boundary of the grain boundary phase to form a Nd2Fe 14 The B main phase grains serve as the core, and the metal carbides formed by carbon segregation serve as the core-shell structure, thus separating the individual Nd2Fe 14 B main phase grains improve the coercive force and other properties of NdFeB magnets.
[0012] In the selection of the first annealing temperature, carbon atoms dissolve in the metal phase of metal carbides within the temperature range of 675-845°C. Too high a temperature will cause carbon atoms to dissolve in the Nd2Fe 14 In the B main phase grains, if the concentration is too low, it will not dissolve; after uniform diffusion, the carbon atoms will slowly segregate from the metal body phase to the outside of the metal phase at the second annealing temperature of 400-500℃. If the second annealing temperature is too high, segregation will not form, and if the temperature is too low, it will cause uneven segregation distribution and incomplete core-shell structure.
[0013] Furthermore, the particle size of the NdFeB magnetic powder is 3-15 μm, the metal carbide is one of rhenium carbide, nickel carbide or aluminum carbide, and the particle size of the metal carbide is 3-7 μm.
[0014] The smaller the crystal core of NdFeB magnet, the stronger its performance. 14 The larger the spacing between the B main phase grains, the better the effect. However, too fine magnetic powder will cause abnormal oxidation during heating, thereby reducing the coercive force.
[0015] Furthermore, the S2 meso-embryo is pressed in a magnetic field of 1.4-2.0 T, the pressing pressure is 220-360 MPa, and the pressing time is 3-5 min.
[0016] Furthermore, the temperature in the S2 heat treatment step is 1030-1075° C., and the time is 3-6 hours, and the temperature in the S3 heat treatment step is 1030-1075° C., and the time is 1-3 hours.
[0017] In the process of grain boundary diffusion, shortening the diffusion time can achieve a better improvement in coercivity.
[0018] Furthermore, the copper diffusion layer of the double diffusion layer in S3 has a thickness of 1-4 μm, and the copper alloy diffusion layer has a thickness of 6-10 μm.
[0019] Furthermore, the composition of the copper alloy is Cu x -REy The alloy, wherein 20<x<30, 70<y<80.
[0020] Furthermore, the RE includes one or a combination of two or more of Dy, Tb, Pr, Sc, Ce, Pm, Tm, and Yb.
[0021] The "wetting" of the grain boundary by copper elements can increase the flow and diffusion rate of RE elements, thereby shortening the heat treatment time and reducing the Nd2Fe 14 B The growth of the main phase grain cell.
[0022] Furthermore, the NdFeB magnet contains the following components in molar percentage: Nd 10-16wt%, Fe 76-84wt%, B 5-9wt%.
[0023] Another object of the present invention is to provide a NdFeB magnet, which is prepared by the above-mentioned preparation method.
[0024] The NdFeB magnet can be used in the fields of power generation, household appliances and motors.
[0025] The beneficial effects of the present invention are:
[0026] 1. The metal carbide used in the present invention is first fully mixed with the magnetic powder particles, and can be evenly penetrated into the interior of the NdFeB magnet during the sintering process. Compared with combining the metal carbide and NdFeB through grain boundary diffusion, the advance mixing not only makes the distribution of each component uniform, but also does not increase the volume of the Nd-rich mobile phase in the grain boundary during the subsequent diffusion of copper and rare earth elements. The Nd-rich phase forms a mobile phase during the heat treatment process, and mainly exists in the triple region between grains. Too much Nd-rich phase in the triple region will dilute the magnetism of the NdFeB magnet, which has a negative effect on the coercive force, remanence and magnetic energy product. Therefore, the above-mentioned mixing of metal carbide and magnetic powder in the present invention and combining with the outer metal elements diffused by the grain boundary can strongly improve the coercive force of the magnet, and also has a good improvement effect on the remanence and magnetic energy product.
[0027] 2. The metal carbide used in the present invention is one of rhenium carbide, nickel carbide or aluminum carbide, wherein the Cu-Re phase formed by metal rhenium and copper atoms has a low melting point and a fast diffusion rate under high temperature heat treatment. 14 The "wetting" of the B main phase grains can produce a better diffusion effect on the outer diffusion layer in the double diffusion layer, so that the rare earth element RE follows the flow of the Cu-Re phase in the grain boundary and diffuses. According to the experimental results in the embodiment, nickel carbide and aluminum carbide can also partially improve the diffusion effect, thereby improving the coercive force and other magnetic properties of the NdFeB magnet.
[0028] 3. The present invention selects metal carbides to mix with NdFeB magnetic powder instead of selecting pure metal or metal oxide for mixing. The use of metal carbides will not affect the formation of a mobile phase with a lower melting point between the metal and the copper element at high temperature, and will also segregate at the subsequent annealing temperature to produce a carbide shell at the grain boundary. The carbide shell is located at the Nd2Fe 14 The B main phase grains are outside the grains, separating the grains from each other, thereby ensuring that the main phase grains will not agglomerate, increasing the orientation of the magnet, and ultimately increasing the coercive force of the NdFeB magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a coercive force curve diagram of the embodiments of the present invention and the comparative example.
[0030] Figure 2 It is a line chart showing the intrinsic coercivity of the embodiments of the present invention and the comparative example. DETAILED DESCRIPTION
[0031] The following will refer to the attached Figure 1 To Attachment Figure 2 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0032] Example 1
[0033] This embodiment provides a neodymium iron boron magnet, and the specific preparation steps are as follows:
[0034] S1. First, prepare a NdFeB main alloy, wherein the specific weight percentage elements are Nd 13wt%, Fe 80wt%, B 6wt%, and other impurity elements account for 1wt%, and the alloys with the above contents are mixed and smelted to obtain a NdFeB main alloy;
[0035] Then, the NdFeB main alloy is crushed and activated, and the NdFeB main alloy is placed in a hydrogen crushing furnace, the vacuum degree is controlled below 1.3Pa, hydrogen is introduced so that the NdFeB main alloy is under a pressure of 0.3Mpa, and the hydrogen crushing treatment is performed for 2 hours. After cooling, the NdFeB main alloy is crushed by a jet mill, and the crushing environment does not contain oxygen, so as to obtain NdFeB main particles with a particle size of 10-12μm;
[0036] Secondly, weigh rhenium carbide powder with a particle size of 5-6 μm, mix the rhenium carbide powder with NdFeB main particles, and the added amount of rhenium carbide is 2% of the weight of the NdFeB main particles.
[0037] S2. Using an isostatic press to press the mixed magnetic powder to form a green embryo, the pressing pressure is 280 MPa, and a 1.6 T magnetic field is applied for orientation, the pressing time is 4 min, and the obtained green embryo is heat-treated at a temperature of 1050 ° C for 4.5 h to obtain a sintered NdFeB permanent magnet;
[0038] S3, the sintered NdFeB permanent magnet is subjected to evaporation plating, the deposited atoms are Cu atoms, the incident energy is 8eV, the deposition rate is 20atom / ps, and the first diffusion layer with a thickness of 2μm is formed; then the second evaporation plating is performed, and the deposited atoms are Cu 25 -Dy 75 Alloy atoms, with incident energy of 8 eV and deposition rate of 16 atom / ps, form a second diffusion layer with a thickness of 8 μm outside the first diffusion layer;
[0039] The preliminary sintering was carried out at a temperature of 1050°C and a time of 2 h.
[0040] S4, performing the first annealing on the double-diffusion layer NdFeB permanent magnet after heat treatment, the first annealing temperature is 750°C, and the time is 2.5 hours; then performing the second annealing, the second annealing temperature is 450°C, and the heat preservation is 4.5 hours to obtain the NdFeB magnet.
[0041] Example 2
[0042] This embodiment provides a neodymium iron boron magnet, and the specific preparation steps are as follows:
[0043] S1. First, prepare a NdFeB main alloy, wherein the specific weight percentage elements are Nd 15wt%, Fe 76wt%, B 9wt%, and other impurity elements account for 1wt%, and the alloys with the above contents are mixed and smelted to obtain a NdFeB main alloy;
[0044] Then, the NdFeB main alloy is crushed and activated, and the NdFeB main alloy is placed in a hydrogen crushing furnace, the vacuum degree is controlled below 1.3Pa, hydrogen is introduced so that the NdFeB main alloy is under a pressure of 0.3Mpa, and the hydrogen crushing treatment is performed for 2 hours. After cooling, the NdFeB main alloy is crushed by a jet mill, and the crushing environment does not contain oxygen, so as to obtain NdFeB main particles with a particle size of 5-8μm;
[0045] Secondly, nickel carbide powder with a particle size of 3-5 μm is weighed, and the nickel carbide powder is mixed with the NdFeB main particles, and the added amount of nickel carbide is 1% of the weight of the NdFeB main particles.
[0046] S2. Using an isostatic press to press the mixed magnetic powder to form a green embryo, the pressing pressure is 220 MPa, and a 1.4 T magnetic field is applied for orientation, the pressing time is 5 min, and the obtained green embryo is heat-treated at a temperature of 1030° C. for 6 h to obtain a sintered NdFeB permanent magnet;
[0047] S3. The sintered NdFeB permanent magnet is subjected to magnetron sputtering treatment using a magnetron sputtering coating machine. The target material is Cu, the working pressure is 0.5 Pa, the current is 10 A, and the target power is 20 W / cm 2 , forming a first diffusion layer with a thickness of 1 μm; then a second magnetron sputtering treatment was carried out, and the target material was Cu 25 -Tb 25 -Pr 50 alloy, working pressure is 0.5Pa, current is 10A, target power is 30W / cm 2 , forming a second diffusion layer with a thickness of 9 μm outside the first diffusion layer;
[0048] The preliminary sintering was carried out at a temperature of 1030°C and a time of 3 h.
[0049] S4. Perform the first annealing on the double-diffusion layer NdFeB permanent magnet after heat treatment, the first annealing temperature is 675°C, and the time is 3 hours; then perform the second annealing, the second annealing temperature is 400°C, and the heat preservation is 5 hours to obtain the NdFeB magnet.
[0050] Example 3
[0051] This embodiment provides a neodymium iron boron magnet, and the specific preparation steps are as follows:
[0052] S1. First, prepare a NdFeB main alloy, wherein the specific weight percentage elements are Nd 10wt%, Fe 84wt%, B 5wt%, and other impurity elements account for 1wt%, and the alloys with the above contents are mixed and smelted to obtain a NdFeB main alloy;
[0053] Then, the NdFeB main alloy is crushed and activated, and the NdFeB main alloy is placed in a hydrogen crushing furnace, the vacuum degree is controlled below 1.3Pa, hydrogen is introduced so that the NdFeB main alloy is under a pressure of 0.3Mpa, and the hydrogen crushing treatment is performed for 2 hours. After cooling, the NdFeB main alloy is crushed by a jet mill, and the crushing environment does not contain oxygen, so as to obtain NdFeB main particles with a particle size of 12-15μm;
[0054] Secondly, aluminum carbide powder with a particle size of 6-7 μm is weighed, and the aluminum carbide powder is mixed with the NdFeB main particles, and the added amount of aluminum carbide is 3% of the weight of the NdFeB main particles.
[0055] S2. Using an isostatic press to press the mixed magnetic powder to form a green embryo, the pressing pressure is 360 MPa, and a 2.0 T magnetic field is applied for orientation, the pressing time is 3 min, and the obtained green embryo is heat-treated at a temperature of 1075 ° C for 3 h to obtain a sintered NdFeB permanent magnet;
[0056] S3, multi-arc ion plating treatment is performed on the sintered NdFeB permanent magnet, the anion plating arc source is Cu, the target current is 50A, and the single ion plating time is 10min, until the first diffusion layer with a thickness of 4μm is formed; then the second multi-arc ion plating treatment is performed, the anion plating arc source is Cu 25 -Sc 40 -Ce 35 alloy atoms, the target current is 50A, and the single ion plating time is 10min, until a second diffusion layer with a thickness of 6μm is formed;
[0057] The preliminary sintering was carried out at a temperature of 1075°C and a time of 1 h.
[0058] S4. Perform the first annealing on the double-diffusion layer NdFeB permanent magnet after heat treatment, the first annealing temperature is 845°C, and the time is 2 hours; then perform the second annealing, the second annealing temperature is 500°C, and the heat preservation is 4 hours to obtain the NdFeB magnet.
[0059] The RE element used as the alloy component of the second diffusion layer in the above embodiment may also be one or a combination of two or more of Pm, Tm, and Yb.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that no metal carbide is added, but the NdFeB magnetic powder is directly sintered to obtain the NdFeB permanent magnetic powder. The specific steps are as follows:
[0062] S1. Prepare a NdFeB main alloy with Nd15wt%, Fe76wt%, B9wt% by weight, and other impurity elements accounting for 1wt%, and mix and melt to obtain a NdFeB main alloy;
[0063] The NdFeB main alloy is hydrogen crushed, cooled and crushed by air flow mill to obtain NdFeB main particles with a particle size of 5-8μm;
[0064] S2. Using an isostatic press to press the mixed magnetic powder to form a green embryo, the pressing pressure is 220 MPa, and a 1.4 T magnetic field is applied for orientation, the pressing time is 5 min, and the obtained green embryo is heat-treated at a temperature of 1030° C. for 6 h to obtain a sintered NdFeB permanent magnet;
[0065] The remaining steps are the same as those in Example 1.
[0066] Comparative Example 2
[0067] The difference between this comparative example and Example 1 lies in the selection of metal carbides, in which a metal phase with a higher melting point is used. The specific differences are as follows:
[0068] S1. First, prepare a NdFeB main alloy, wherein the specific weight percentage elements are Nd 13wt%, Fe 80wt%, B 6wt%, and other impurity elements account for 1wt%, and the alloys with the above contents are mixed and smelted to obtain a NdFeB main alloy;
[0069] Then, the NdFeB main alloy is crushed and activated, and the NdFeB main alloy is placed in a hydrogen crushing furnace, the vacuum degree is controlled below 1.3Pa, hydrogen is introduced so that the NdFeB main alloy is under a pressure of 0.3Mpa, and the hydrogen crushing treatment is performed for 2 hours. After cooling, the NdFeB main alloy is crushed by a jet mill, and the crushing environment does not contain oxygen, so as to obtain NdFeB main particles with a particle size of 10-12μm;
[0070] Secondly, weigh tungsten carbide powder with a particle size of 5-6 μm, mix the tungsten carbide powder with the NdFeB main particles, and the added amount of tungsten carbide is 2% of the weight of the NdFeB main particles.
[0071] The remaining steps are the same as those in Example 1.
[0072] Comparative Example 3
[0073] The difference between this comparative example and Example 1 is that the addition ratio of metal carbide is enlarged, and the specific differences are as follows:
[0074] S1. First, prepare a NdFeB main alloy, wherein the specific weight percentage elements are Nd 13wt%, Fe 80wt%, B 6wt%, and other impurity elements account for 1wt%, and the alloys with the above contents are mixed and smelted to obtain a NdFeB main alloy;
[0075] Then, the NdFeB main alloy is crushed and activated, and the NdFeB main alloy is placed in a hydrogen crushing furnace, the vacuum degree is controlled below 1.3Pa, hydrogen is introduced so that the NdFeB main alloy is under a pressure of 0.3Mpa, and the hydrogen crushing treatment is performed for 2 hours. After cooling, the NdFeB main alloy is crushed by a jet mill, and the crushing environment does not contain oxygen, so as to obtain NdFeB main particles with a particle size of 10-12μm;
[0076] Secondly, weigh rhenium carbide powder with a particle size of 5-6 μm, mix the rhenium carbide powder with NdFeB main particles, and the added amount of rhenium carbide is 5% of the weight of the NdFeB main particles.
[0077] The remaining steps are the same as those in Example 1.
[0078] Comparative Example 4
[0079] The difference between this comparative example and Example 1 is that a single-layer diffusion layer is processed on the outer surface of the sintered NdFeB permanent magnet. The specific differences are as follows:
[0080] S3, performing evaporation plating on the sintered NdFeB permanent magnet, wherein the deposited atoms are Cu atoms, the incident energy is 8 eV, the deposition rate is 20 atom / ps, and a single diffusion layer with a thickness of 10 μm is formed;
[0081] The preliminary sintering was carried out at a temperature of 1050°C and a time of 2 h.
[0082] The remaining steps are the same as those in Example 1.
[0083] Comparative Example 5
[0084] The difference between this comparative example and Example 1 is that a single-layer diffusion layer is processed on the outer surface of the sintered NdFeB permanent magnet. The specific differences are as follows:
[0085] S3, evaporation plating treatment is performed on the sintered NdFeB permanent magnet, and the deposited atoms are Cu 25 -Dy 75 Alloy atoms, with an incident energy of 8 eV and a deposition rate of 16 atom / ps, form a single diffusion layer with a thickness of 10 μm;
[0086] The preliminary sintering was carried out at a temperature of 1050°C and a time of 2 h.
[0087] The remaining steps are the same as those in Example 1.
[0088] Comparative Example 6
[0089] The difference between this comparative example and Example 1 is that the annealing temperature and the number of times of the NdFeB permanent magnet covered with a double diffusion layer after heat treatment are changed, and the specific changes are as follows:
[0090] S4, performing the first annealing on the double-diffusion layer NdFeB permanent magnet after heat treatment, the first annealing temperature is 600°C, and the time is 2.5 hours; then performing the second annealing, the second annealing temperature is 450°C, and the heat preservation is 4.5 hours to obtain the NdFeB magnet.
[0091] The remaining steps are the same as those in Example 1.
[0092] Comparative Example 7
[0093] The difference between this comparative example and Example 1 is that the annealing temperature and the number of times of the NdFeB permanent magnet covered with a double diffusion layer after heat treatment are changed, and the specific changes are as follows:
[0094] S4, performing the first annealing on the double-diffusion layer NdFeB permanent magnet after heat treatment, the first annealing temperature is 750°C, and the time is 2.5 hours; then performing the second annealing, the second annealing temperature is 350°C, and the heat preservation is 4.5 hours to obtain the NdFeB magnet.
[0095] The remaining steps are the same as those in Example 1.
[0096] Comparative Example 8
[0097] The difference between this comparative example and Example 1 is that the annealing temperature and the number of times of the NdFeB permanent magnet covered with a double diffusion layer after heat treatment are changed, and the specific changes are as follows:
[0098] S4, performing an annealing on the double-diffusion-layer NdFeB permanent magnet after heat treatment, wherein the annealing temperature is 550° C. and the time is 2.5 h to obtain a NdFeB magnet.
[0099] The remaining steps are the same as those in Example 1.
[0100] Experiments and data
[0101] The NdFeB magnets prepared in the above examples and comparative examples were tested for coercivity, remanence, intrinsic coercivity and maximum magnetic energy product. The test results are shown in Table 1 below:
[0102]
[0103] The above blank control is only sintered from the most common NdFeB magnet, without any other processing steps. The specific weight percentage elements are Nd13wt%, Fe80wt%, B6wt%, and other impurity elements account for 1wt%. The alloys with the above contents are mixed and smelted to obtain the NdFeB main alloy.
[0104] The coercive forces of the embodiments and comparative examples are plotted in line graphs to obtain Figure 1 .
[0105] The intrinsic coercivity of each embodiment and comparative example is plotted as a line graph to obtain Figure 2 .
[0106] Remanence: Br / T, coercivity Hcb / kOe, intrinsic coercivity Hcj / kOe, maximum magnetic energy product (BH)max / MGOe.
[0107] analyze
[0108] The data in Table 1 show that the remanence of the NdFeB magnets prepared in Examples 1-3 of the present application is highly improved, the coercive force and the intrinsic coercive force are greatly improved, and the maximum magnetic energy product is also correspondingly improved, which can comprehensively improve the comprehensive performance of the NdFeB magnets.
[0109] Compared with the untreated blank group magnets, Example 1 of the present invention has an improvement of 0.8T in remanence, 15.7kOe in coercivity, 24.8kOe in intrinsic coercivity, and 11.1MGOe in maximum magnetic energy product; while the remanence of the magnet of Comparative Example 1 has an improvement of 0.2T, 2.5kOe in coercivity, 3.4kOe in intrinsic coercivity, and 2.1MGOe in maximum magnetic energy product. In comparison, the improvement of Example 1 is greatly greater than that of the blank group magnets. The present invention uses technical means such as adding a double diffusion layer of metal carbide and copper and corresponding annealing temperature to achieve a greater and better performance improvement.
[0110] No metal carbide is added to the NdFeB magnetic powder of Comparative Example 1. The NdFeB magnet prepared in Comparative Example 1 is obviously inferior to those of Example 1 of the present application in terms of remanence, coercive force, intrinsic coercive force and maximum magnetic energy product, which indicates that the addition of metal carbide to the NdFeB magnet in the present application is very important for comprehensively improving the comprehensive performance of the NdFeB magnet.
[0111] The raw material used for the additive metal carbide in Comparative Example 2 is tungsten carbide powder, and the remaining steps are the same as those in Example 1. The tungsten carbide used is not significantly improved compared with materials such as rhenium carbide, nickel carbide and aluminum carbide. The melting point of tungsten in tungsten carbide is extremely high, and the metal phase formed between the grain boundary and copper has poor fluidity, and a good grain boundary cannot be formed. The data in Table 1 show that the remanence and coercive force of Comparative Example 1 have a certain improvement, but it is only the degree of improvement of ordinary grain boundary diffusion, which relies on the characteristics of the diffusion layer and the tungsten material itself, and the synergistic effect is not large, indicating that the metal carbide and the diffusion layer of the embodiment of the present invention can have a synergistic diffusion effect, thereby greatly improving the performance of the magnet.
[0112] The addition ratio of metal carbides in Comparative Example 3 is increased to 5%, and the remaining steps are the same as those in Example 1. The NdFeB magnet prepared in Comparative Example 3 is very close to the comprehensive performance of Example 3 in terms of remanence, coercive force and maximum magnetic energy product, but the related improvements have not reached the limit, indicating that more metal carbides will affect the improvement of the comprehensive performance and the uniformity of grain boundary distribution.
[0113] In comparative example 4, only a single copper atomic layer was used for diffusion during diffusion layer treatment, and no outer alloy layer treatment was performed. Compared with example 1, the performance improvement was close, but the corresponding effect was not achieved. This shows that the combination of metal carbide and copper can be diffused well, and the segregation of metal carbide to form a core-shell structure has nothing to do with the diffusion layer, but is related to the annealing temperature, which can effectively improve the coercive force.
[0114] Comparative Example 5 does not perform the first layer of pure copper plating, but directly performs the copper alloy plating. The data in Table 1 show that compared with the improvement effect of Comparative Example 4, the comprehensive performance of the magnet prepared in Comparative Example 5 is improved more, but less than the improvement effect of Example 1. The reason is that the diffusion of copper elements does not fully wet the grain boundaries, so that the rare earth elements in the alloy components and Nd2Fe 14 The B main phase grains were not fully replaced and no (Nd-RE)Fe 14 In B-type grains, the rare earth elements are only present at the edges of the grain boundaries, so the overall performance is not as good as that of the embodiments of the present application.
[0115] In comparative example 6, when the first annealing is performed, the annealing temperature is lowered to 600°C, and the remanence improvement performance is better, but the coercive force and intrinsic coercive force are poorly improved. Compared with the data test of embodiment 1, it can be explained that the first annealing and the related annealing temperature of the present application can fully disperse the carbon atoms, and have a better dispersion effect for the subsequent second annealing to segregate the carbon atoms.
[0116] In Comparative Example 7, the temperature is lowered to 350°C during the second annealing. The data show that the coercive force is partially improved compared with that of Comparative Example 6, and the remanence is slightly reduced. Since the second annealing is the temperature for forming segregation, it can be explained that if the second annealing temperature is too low, it will make it more difficult for carbon to segregate in the metal crystal phase, and it will be impossible to form a complete and sufficient core-shell structure, so the magnet-related performance is low.
[0117] Comparative Example 8 did not perform two annealings, but directly used conventional annealing operations. The NdFeB magnet prepared in this comparative example had the smallest performance improvement, indicating that basically no core-shell structure was generated, and the coercive force and intrinsic coercive force were improved very little.
[0118] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. A method for preparing a neodymium iron boron magnet, characterized in that: The specific steps include: S1. Smelting the alloy raw material into alloy flakes, crushing by hydrogen to obtain NdFeB magnetic powder, mixing the NdFeB magnetic powder with metal carbide, wherein the addition ratio of the metal carbide is 1-3% of the weight of the NdFeB magnetic powder, and the metal carbide is one of rhenium carbide, nickel carbide or aluminum carbide; S2, the mixed magnetic powder is pressed to form a green embryo, and the green embryo is heat-treated to obtain a sintered NdFeB permanent magnet; S3, sequentially using copper and copper alloy as deposition atoms, target materials or negative ion plating arc sources to perform double-layer evaporation plating, magnetron sputtering plating or multi-arc ion plating on the sintered NdFeB permanent magnet to form a double-layer diffusion layer, and performing heat treatment again, wherein the first layer of the double-layer diffusion layer is a copper diffusion layer, and the second layer is a copper alloy diffusion layer; S4. Perform the first annealing on the NdFeB permanent magnet covered with the double diffusion layer, the annealing temperature is 675-845°C, and the time is 2-3h; then perform the second annealing at a temperature of 400-500°C and keep the temperature for 4-5h to obtain the NdFeB magnet.
2. The method for preparing a NdFeB magnet according to claim 1, characterized in that: The particle size of the NdFeB magnetic powder is 3-15 μm, and the particle size of the metal carbide is 3-7 μm.
3. The method for preparing a NdFeB magnet according to claim 1, characterized in that: The S2 meso-embryo is pressed in a magnetic field of 1.4-2.0 T, the pressing pressure is 220-360 MPa, and the pressing time is 3-5 min.
4. The method for preparing a NdFeB magnet according to claim 1, characterized in that: The temperature in the S2 heat treatment step is 1030-1075° C. and the time is 3-6 hours. The temperature in the S3 heat treatment step is 1030-1075° C. and the time is 1-3 hours.
5. The method for preparing a NdFeB magnet according to claim 1, characterized in that: The thickness of the copper diffusion layer is 1-4 μm, and the thickness of the copper alloy diffusion layer is 6-10 μm.
6. The method for preparing a NdFeB magnet according to claim 1, characterized in that: The composition of the copper alloy is Cu x -RE y Alloy, wherein 20<x<30, 70<y<80.
7. The method for preparing a NdFeB magnet according to claim 6, characterized in that: The RE includes one or a combination of two or more of Dy, Tb, Pr, Sc, Ce, Pm, Tm, and Yb.
8. The method for preparing a NdFeB magnet according to claim 7, characterized in that: The NdFeB magnet contains the following components in molar percentage: Nd 10-16wt%, Fe 76-84wt%, B 5-9wt%.
9. A neodymium iron boron magnet, characterized in that: The NdFeB magnet is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the NdFeB magnet as claimed in claim 9, characterized in that: The NdFeB magnet is used in the fields of power generation and household appliances.
Citation Information
Patent Citations
High-temperature neodymium-iron-boron permanent magnet and grain boundary diffusion preparation method thereof
CN117012537A
Bonded neodymium iron boron-ferrite permanent magnet and preparation method and application thereof
CN117831926A
Method for manufacturing ferromagnetic core containing modified aluminum carbide
CN103295766A
Nanocrystalline thermal deformation rare-earth permanent magnet material with high coercivity and preparation method of nanocrystalline thermal deformation rare-earth permanent magnet material
CN105321645A